Liturgical Manuscripts Preserved in Hungarian Libraries: A Survey of Sacramentaries, Missals, Lectionaries - Strittmatter, Anselm (Traditio, 1963)
‘Notre époque a vu bien des sécularlsations, sur le bienfait desquelles on n'a pas toujours été d'accord. Il me semble que la sécularisation de la liturgie ne choquerait personne et que tous les esprits droits y verraient un progrès vers une vérité plus entière.’ Thus wrote the late Michel Andrieu in 1948 at the conclusion of his ‘avant-propos’ to the second volume of his great edition, Les Ordines Romani du haut moyen âge. ‘Secularization’ is a strange word to apply to the critical study of any subject, be it ever so sacred, but it is obvious that the distinguished author considered his work part of a progressive movement, one which indeed he had himself promoted and was promoting as few other men of our time. This movement may be said to have begun with the publication of Léopold Delisle's famous Métnoire sur d'anciens sacramentaires, published in 1886 in the Mémoires de l'Académic des inscriptions et bellesletires.